Unsaturated polyester composites filled with untreated and surface treatment sugarcane bagasse by hot press technique / Muhammad Salihin Zakaria. - Muhammad Salihin Zakaria (School of Materials Engineering, Universiti Malaysia Perlis, 2009)
The aim of this research is the improvement of the mechanical properties of natural fiber reinforced thermoset, as a result of optimization of the properties of sugarcane bagasse fibers by the use of NaOH treatment process. Tert-butyl perbenzoate was used as catalyst at elevated temperature for efficient processing of polyester composites. Sugarcane bagasse fibers were alkalized with 1, 3 and 5% NaOH solution, combined with four different fiber loading formulation, and hot-pressed to form natural fibers composites. The flexural modulus and strength of bagasse fiber composites alkalized with 3% NaOH solution gave the highest value and the untreated bagasse fiber gave the lowest. The same trend was obtained for the tensile modulus and strength as expected. However, by increased the NaOH solution, the mechanical properties decreased as a result of fibrillation lead to uneffective stress transfer occurred. Meanwhile, the break elongation of composites was decreased due to the improved fiber-matrix adhesion (to give more stiffness to the composites). Dynamic mechanical analysis (DMA) showed that with 3% NaOH solution treatment, bagasse fiber composites gave the highest storage modulus (E') values and the lowest tan delta values. SEM observations on the fracture surface of composites showed that the surface modification of the fiber occurred and improved fiber-matrix adhesion. A water absorption test also showed that with 3% NaOH solution treatment, bagasse fiber composites gave higher bonding and adhesion compared to all another bagasse fiber composites.